Place Branding - Barreto, Ana Margarida (2022)
Esta obra tem como objectivo dar a conhecer a investigação na área do Place Branding em países de língua portuguesa e espanhola, em torno de três temáticas: City Branding; Destination Branding e Nation Branding). Surge no âmbito de duas primeiras edições da Conferência Ibero-Americana de Place Branding, organizadas pelo GI em Comunicação Estratégica e Processos de Tomada de Decisão do Instituto de Comunicação da Nova. This work aims to present research in the area of Place Branding in Portuguese and Spanish-speak-ing countries, around three themes: City Branding; Destination Branding and Nation Branding). It comes within the scope of the first two editions of the Ibero-American Conference on Place Branding, organized by the Research Group on Strategic Communication and Decision-Making Processes of the Instituto de Comunicação da Nova.